Tactical management features of Ukrainian business in the conditions of war (Economics and region, 2024)
This article discusses the management of entrepreneurship in the conditions of war in Ukraine. The purpose of this study is to analyse the tactical management of business activities in Ukraine in the conditions of war. The study seeks to identify the impact of military events on the tactical aspects of enterprise management and to determine effective adaptation strategies. The study’s significance lies in developing recommendations and strategies to improve enterprise resilience and efficiency in unpredictable conditions. These recommendations facilitate the practical application of knowledge and help enterprises manage their activities effectively in challenging conditions, contributing to their sustainable functioning and development. The article outlines the research methods used to study the tactical management of businesses in Ukraine during wartime. It suggests recommendations for optimising the tactical management of enterprises to ensure their sustainability and development.
Keywords: entrepreneurship; tactical management; government initiatives; adaptation; effective strategies; economic situation; war